2011
DOI: 10.1128/iai.05022-11
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha Production from CD8+T Cells Mediates Oviduct Pathological Sequelae following Primary Genital Chlamydia muridarum Infection

Abstract: The immunopathogenesis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
136
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 43 publications
13
136
3
2
Order By: Relevance
“…A recent study by Murthy and colleagues showed that wt and CD8 ϩ T knockout mice displayed similar clearances of C. muridarum following vaginal chlamydial challenge (95). These data support previous studies demonstrating that CD8 ϩ T cells are not critical for C. trachomatis clearance (45,59,96).…”
Section: T Cellssupporting
confidence: 81%
“…A recent study by Murthy and colleagues showed that wt and CD8 ϩ T knockout mice displayed similar clearances of C. muridarum following vaginal chlamydial challenge (95). These data support previous studies demonstrating that CD8 ϩ T cells are not critical for C. trachomatis clearance (45,59,96).…”
Section: T Cellssupporting
confidence: 81%
“…CD8 ϩ T cells are not required for resolution of primary infection or immunity to reinfection, but they can contribute to protection via IFN-␥ release (33). Nonetheless, it was recently demonstrated that CD8 ϩ T cell production of tumor necrosis factor alpha (TNF-␣) promotes oviduct pathology following primary murine genital tract infection (34). Antibodies and B cells are also not necessary for eradication of primary infection (35,36), but they play an important role in resistance to chlamydial reinfection (37).…”
Section: Mouse Modelsmentioning
confidence: 99%
“…The molecular basis for this attenuation is unclear but could involve plasmid-regulated genes (13) that function as Toll-like receptor 2 (14) or tumor necrosis factor alpha (TNF-␣) receptor antagonists (15,16). On the other hand, the basis of plasmid-mediated pathology might be a direct host-pathogen relationship caused by infection with virulent plasmid-bearing organisms.…”
mentioning
confidence: 99%